Singularity-free theory and adaptive finite element computations of arbitrarily-shaped dislocation loop dynamics in 3D heterogeneous material structures. (October 2022) - Vattré, A.; Chiaruttini, V.
Abstract: The long-standing problem of arbitrarily-shaped discrete dislocation loops in three-dimensional heterogeneous material structures is addressed by introducing novel singularity-free elastic field solutions as well as developing adaptive finite element computations for dislocation dynamics simulations. The first framework uses the Stroh formalism in combination with the biperiodic Fourier-transform and dual variable and position techniques to determine the finite-valued Peach–Koehler force acting on curved dislocation loops. On the other hand, the second versatile mixed-element method proposes to capture the driving forces through dissipative energy considerations with domain integrals by means of the virtual extension principle of the surfacial discontinuities. Excellent agreement between theoretical and numerical analyses is illustrated from simple circular shear dislocation loops to prismatic dislocations with complicated simply-connected contours in linear homogeneous isotropic solids and anisotropic elastic multimaterials, which also serves as improved benchmarks for dealing with more realistic boundary-value problems with evolving dislocations. Examples of sophisticated dislocation applications include the short-range core reaction between intersecting dislocation loops in interaction with a spherical cavity, as well as the Orowan dislocation-precipitate bypass mechanism in a compressed micropillar of polycrystalline copper. The latter multiscale investigation spans three orders of magnitude in size scale, and is thus enabled by computationally efficient and robust adaptive mesh generation procedures for explicit dislocation propagation, interaction, and coalescence in three-dimensional materials and material structures.